Strengthening Digital Branding for Creative Economy Business Actors - Lina Susilowati; Shanti Nugroho; Munawaroh; Putri Fatmawati (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The issue of digital branding is very relevant along with the development of innovative technology. Digital branding helps creative economy business actors to interact with customers to create loyalty. This creative economy business is called